Genome sequence of Perigonia lusca single nucleopolyhedrovirus: insights into the evolution of a nucleotide metabolism enzyme in the family Baculoviridae - Ardisson-Araujo, Daniel M. P.; Lima, R. N.; Melo, F. L.; Clem, R. J.; Huang, Ning; Bao, S. N.; Sosa-Gomez, D. R.; Ribeiro, B. M. (My University, 2017)
The genome of a novel group II alphabaculovirus, Perigonia lusca single nucleopolyhedrovirus (PeluSNPV), was sequenced and shown to contain 132,831 bp with 145 putative ORFs (open reading frames) of at least 50 amino acids. An interesting feature of this novel genome was the presence of a putative nucleotide metabolism enzyme-encoding gene (pelu112). The pelu112 gene was predicted to encode a fusion of thymidylate kinase (tmk) and dUTP diphosphatase (dut). Phylogenetic analysis indicated that baculoviruses have independently acquired tmk and dut several times during their evolution. Two homologs of the tmk-dut fusion gene were separately introduced into the Autographa californica multiple nucleopolyhedrovirus (AcMNPV) genome, which lacks tmk and dut. The recombinant baculoviruses produced viral DNA, virus progeny, and some viral proteins earlier during in vitro infection and the yields of viral occlusion bodies were increased 2.5-fold when compared to the parental virus. Interestingly, both enzymes appear to retain their active sites, based on separate modeling using previously solved crystal structures. We suggest that the retention of these tmk-dut fusion genes by certain baculoviruses could be related to accelerating virus replication and to protecting the virus genome from deleterious mutation.
Citation: Ardisson-Araujo, D. M. P., Lima, R. N., Melo, F. L., Clem, R. J., Huang, N., Bao, S. N., . . . Ribeiro, B. M. (2016). Genome sequence of Perigonia lusca single nucleopolyhedrovirus: insights into the evolution of a nucleotide metabolism enzyme in the family Baculoviridae. Scientific Reports, 6, 14. doi:10.1038/srep24612
Keywords: Virus Dutpase; Saccharomyces-Cerevisiae; Replication; Gene; Identification; Granulovirus